2005
DOI: 10.1097/00004850-200511000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Amisulpride versus quetiapine for the treatment of delirium: a randomized, open prospective study

Abstract: The present study aimed to: (i) provide preliminary data on the effectiveness and tolerability of atypical antipsychotics, amisulpride (AMSP) and quetiapine (QTP) for patients with delirium and (ii) investigate whether the two drugs affect sleep differently and further relation with the recovery time of delirium. Forty patients with delirium were randomly assigned to either AMSP or QTP groups, with a flexible dosing schedule. The Delirium Rating Scale-revised-98 (DRS-R-98) and clinical global impression-severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 18 publications
5
73
0
9
Order By: Relevance
“…Skrobik et al [89] demonstrated that olanzapine was a safe alternative to haloperidol for delirious patients in the ICU with similar clinical improvement and less EPS. Similar results have been demonstrated in smaller, non-placebo-controlled studies with amisulpride [90], quetiapine [90,91], and risperidone [92,93]. Recently, a prospective, single-blind, randomized controlled trial compared the efficacy and safety of haloperidol, olanzapine, and risperidone in the treatment of delirium with 20 to 23 patients in each arm of the study [94].…”
Section: Atypical Anti-psychoticssupporting
confidence: 66%
“…Skrobik et al [89] demonstrated that olanzapine was a safe alternative to haloperidol for delirious patients in the ICU with similar clinical improvement and less EPS. Similar results have been demonstrated in smaller, non-placebo-controlled studies with amisulpride [90], quetiapine [90,91], and risperidone [92,93]. Recently, a prospective, single-blind, randomized controlled trial compared the efficacy and safety of haloperidol, olanzapine, and risperidone in the treatment of delirium with 20 to 23 patients in each arm of the study [94].…”
Section: Atypical Anti-psychoticssupporting
confidence: 66%
“…Le linee guida NICE 20 identificano come significativi tre studi (Hu, 2006;Lee, 2005;. Lo studio di Hu 21 e quello di Lee 22 focalizzavano l'attenzione sul trattamento del delirium nei pazienti ospedalizzati, eslcudendo quelli ricoverati in terapia intensiva.…”
Section: Farmaci Antipsicoticiunclassified
“…Estudios encontrados que han evaluado la efectividad de la quetiapina como tratamiento del delirium. [37][38][39][40][41][42][43] • Seis eran estudios específicos que abordaban la efectividad de la quetiapina como tratamiento del delirium [7,[44][45][46][47][48] …”
Section: Búsqueda De La Evidenciaunclassified
“…Lee et al [47] realizaron un estudio abierto, randomizado, con dosis flexibles de quetiapina y amisulpride, que pretendía comparar la eficacia (medida con la DRS-R-98) y tolerabilidad de ambos fármacos y de forma secundaria valorar su repercusión sobre medidas subjetivas de sueño. De los 40 individuos que iniciaron el estudio, 31 lo finalizaron (77.5%) (15 en grupo de quetiapina y 16 en el de amisulpride), los cuales no mostraron diferencias en parámetros sociodemográficos.…”
Section: Análisis De La Validez De La Evidenciaunclassified